Functional shift with maintained regenerative potential following portal vein ligation. Issue 1 (December 2017) - Kovács, Tibor; Máthé, Domokos; Fülöp, András; Jemnitz, Katalin; Bátai-Konczos, Attila; Veres, Zsuzsanna; Török, György; Veres, Dániel; Horváth, Ildikó; Szigeti, Krisztián; Homolya, László; Szijártó, Attila
Abstract Selective portal vein ligation (PVL) allows the two-stage surgical resection of primarily unresectable liver tumours by generating the atrophy and hypertrophy of portally ligated (LL) and non-ligated lobes (NLL), respectively. To evaluate critically important underlying functional alterations, present study characterisedin vitro andvivo liver function in male Wistar rats (n = 106; 210–250 g) before, and 24/48/72/168/336 h after PVL. Lobe weights and volumes by magnetic resonance imaging confirmed the atrophy-hypertrophy complex. Proper expression and localization of key liver transporters (Ntcp, Bsep) and tight junction protein ZO-1 in isolated hepatocytes demonstrated constantly present viable and well-polarised cells in both lobes.In vitro taurocholate and bilirubin transport, as well asin vivo immunohistochemical Ntcp and Mrp2 expressions were bilaterally temporarily diminished, whereas LL and NLL structural acinar changes were divergent.In vivo bile and bilirubin-glucuronide excretion mirrored macroscopic changes, whereas serum bilirubin levels remained unaffected.In vivo functional imaging (indocyanine-green clearance test;99m Tc-mebrofenin hepatobiliary scintigraphy; confocal laser endomicroscopy) indicated transitionally reduced global liver uptake and -excretion. While LL functional involution was permanent, NLL uptake and excretory functions recovered excessively. Following PVL, functioning cells remain even in LL. Despite extensive bilateral morpho-functional changes, NLL functional increment restores temporary declined transport functions, emphasising liver functional assessment.